Early prenatal screening in Iceland and Norway - Background and current situation - Fjose, Maria; Halle, Kristine Flo (NTNU, 2017)
Abstract In our project, the aim has been to explore early prenatal screening in Iceland and Norway. Seen from the outside, these two countries have a lot in common. They are both Nordic democratic welfare states, with several common historical and cultural roots. Despite this, there are significant differences in the use of prenatal screening (1). An interesting question is, whether the differences in Iceland and Norway can be seen as an incidental result of different political systems and laws, organisation of the health care system, or whether we are in fact facing deeper cultural differences. To gain deeper insight into these topics, we have performed a project with two distinct elements. Using data from an empirical study, we have tried to explore the use of early ultrasound and prenatal screening among Icelandic women, and what characterises those who choose to undergo the screening. To put the empirical study in a perspective, we have done some field work both in Iceland and Norway. The design of the report To distinguish the two elements of the project properly, we have divided the report in part one and part two. These two parts are made in a way so they can be read separate. With other words, they will both contain their own introduction, background, method, findings/results and discussion. Part two will hopefully lead to a publication, and is therefore designed as a scientific paper. Part one – exploring the field The essence of part one is the field work, with semi-structured interviews of health personnel, professionals and pregnant women in Iceland and Norway. Our focus was their personal experience and thoughts around prenatal screening and antenatal care. For a better understanding of the situation in the two countries, we have tried to explain how the health care system works, what diagnostic methods that are used and the regulation of the screening, in the background. We have also mentioned the most common anomalies the screening is searching for, and how abortion in the two countries is ...